Circulating ANGPTL8 Is Associated with the Presence of Metabolic Syndrome and Insulin Resistance in Polycystic Ovary Syndrome Young Women - Danlan Pu; Ling Li; Jingxia Yin; Rui Liu; Gangyi Yang; Yong Liao; Qinan Wu (Mediators of Inflammation)
Background. ANGPTL8 has been reported to be a regulator of lipid metabolism, and it is associated with insulin resistance (IR) and metabolic syndrome (MetS). We investigated whether ANGPTL8 plays a role in MetS. Methods. ANGPTL8 and adiponectin concentrations were measured in PCOS patients with or without MetS and in their corresponding healthy controls. The association of circulating ANGPTL8 with adiponectin and other parameters was also examined. Results. Circulating ANGPTL8 concentrations were higher in PCOS women with MetS than in those without MetS and in the controls (P<0.01). ANGPTL8 was positively correlated with age, BMI, FAT%, WHR, SBP, TG, FBG, HbA1c, Fins, and HOMA-IR (all P<0.01) in the study populations and negatively associated with adiponectin and M-values (P<0.001). In addition, ANGPTL8 was positively correlated with PRL, LH, TEST, and FAI and negatively correlated with SHBG (all P<0.01). ROC curve analyses showed that the AUCMetS was 0.87 (P<0.001), with a sensitivity of 92.4% and specificity of 75.4%, and the AUCIR was 0.82 (P<0.01), with a sensitivity of 76.4% and specificity of 75.6%. Conclusion. ANGPTL8 levels progressively decrease from PCOS patients with MetS to those without MetS and may be a serum marker associated with the degree of metabolic disorders.